2021
DOI: 10.1080/15140326.2021.1928421
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette price elasticity in Croatia – analysis of household budget surveys

Abstract: This study estimates both conditional and unconditional cigarette price elasticity of quantity demanded in Croatia. Authors use Deaton's method, also known as the Almost Ideal Demand-System (AIDS), to obtain consistent estimates of the cigarette price elasticity on the sample of Croatian households. The data from household surveys (HBS) conducted in Croatia for three periods (2010, 2011 and 2014 year) is provided by the Croatian Bureau of Statistics (CBS). Estimated unconditional cigarette price elasticity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The estimated price elasticity is −1.01 and implies that an increase in cigarette prices by 10% leads to a decrease in cigarette consumption by 10.1%. Compared with the price elasticity estimates for Serbia,23 Montenegro24 and Croatia,25 where unconditional (total) price elasticity amounted to −0.64 to –0.8 and −1.38, respectively, it can be concluded that our estimated price coefficient is in line with research in similar neighbouring countries. Roughly about 55% of the negative effect of price growth on the overall demand comes from a decrease in smoking prevalence and 45% from a decrease in the quantity of cigarettes consumed by those who smoke.…”
Section: Discussionsupporting
confidence: 78%
“…The estimated price elasticity is −1.01 and implies that an increase in cigarette prices by 10% leads to a decrease in cigarette consumption by 10.1%. Compared with the price elasticity estimates for Serbia,23 Montenegro24 and Croatia,25 where unconditional (total) price elasticity amounted to −0.64 to –0.8 and −1.38, respectively, it can be concluded that our estimated price coefficient is in line with research in similar neighbouring countries. Roughly about 55% of the negative effect of price growth on the overall demand comes from a decrease in smoking prevalence and 45% from a decrease in the quantity of cigarettes consumed by those who smoke.…”
Section: Discussionsupporting
confidence: 78%